2019
DOI: 10.18823/asiatefl.2019.16.4.26.1422
|View full text |Cite
|
Sign up to set email alerts
|

Literature-Circles-Based Cooperative Writing : From the Perceptions of Indonesian University EFL Learners with Writing Anxiety

Abstract: Writing anxiety is conceptualized by Jang and Choi (2014) as "a fear of the writing process that outweighs the projected gain from the ability to gain (p. 82)." This hinders the learners" potential to be successful in performing English writing from the very beginning of the reading-writing learning process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The current results warrant further investigation via creating introvert-friendly opportunities to encourage students to write dialogue journals in which they record their thoughts and experiences in an informal manner (Jacobs and Renandya 2019 ). Further studies should investigate using CRS in write responses (Cheng and Wang 2019 ), literature circles in online cooperative writing for learners with writing anxiety (Lubis and Rahmawati 2019 ), and authentic multimodal implementations (Isazadeh et al 2016 ). On this basis, it can be concluded that this study adds to the research literature in understanding the nature of the relationship between introverts and extroverts and their social presence and sense of connectedness within the online writing environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current results warrant further investigation via creating introvert-friendly opportunities to encourage students to write dialogue journals in which they record their thoughts and experiences in an informal manner (Jacobs and Renandya 2019 ). Further studies should investigate using CRS in write responses (Cheng and Wang 2019 ), literature circles in online cooperative writing for learners with writing anxiety (Lubis and Rahmawati 2019 ), and authentic multimodal implementations (Isazadeh et al 2016 ). On this basis, it can be concluded that this study adds to the research literature in understanding the nature of the relationship between introverts and extroverts and their social presence and sense of connectedness within the online writing environment.…”
Section: Discussionmentioning
confidence: 99%
“…Further research suggested implementing authentic video materials to facilitate the introverts’ and extroverts’ learning processes (Isazadeh et al 2016 ). Lubis and Rahmawati ( 2019 ) proposed using literature circles that include individual responsibility and promotive communication to mediate the implementation of collaborative writing for learners with writing anxiety. Above all, provision of emotional support and personality equity plays a crucial role in the introverted decision-making process (Tao et al 2020 ).…”
Section: The Literature Reviewmentioning
confidence: 99%
“…After peer debriefing process (Janesick, 2015), the findings of this study revealed that learners' low level of writing skill, confidence, self-efficacy, self-esteem, and grammatical knowledge, gender, instructor's negative feedback, and writing motivation appeared as the major factors contributing to shape their anxiety feelings during essay writing processes. It can be inferred that learners' writing anxiety was significantly affected by both internal and external factors (Lubis & Rahmawati, 2019). The findings also reported that those negative feelings were significantly affect learners' writing performance and achievement.…”
Section: Discussionmentioning
confidence: 77%
“…For some scholars, age, gender, learners' writing ability (McLeod, 1987), writing strategies (Salovey, 1990), and linguistic insecurity (Holland, 2014) are the dominant factors contributing to shaping these negative feelings. Similarly, a recent study (Lubis & Rahmawati, 2019) also claimed that such situation can reduce writing productivity and hinder learners' potential to achieve a successful English writing performance. For some scholars, writing anxiety has a negative relationship with learners' writing performance and competency (Daly & Miller, 1975;Faigley et al, 1981).…”
Section: Introductionmentioning
confidence: 97%
“…The students can develop their reading comprehension skills (Fredricks & McColsky 2012;Lubis, 2018;Moen, 2004;Nurjati, 2013;Widodo, 2015), writing skills particularly the development of cohesion and coherence usage (Lubis, 2018), and meaningmaking skills (Widodo, 2015). Some essential soft skills can also be gained by the students encompassing collaborative strategies (Lubis, 2018;Lubis & Rahmawati, 2019;Moen, 2004;Sheltonstrong, 2012;Widodo, 2015), critical thinking (Fredricks & McColskey, 2012;Lubis, 2019;Lubis & Rahmawati, 2019;Maher, 2013), and cultural awareness (Iida, 2013;Moecharam & Sari, 2014).…”
Section: Introductionmentioning
confidence: 99%